Necesidad de unificaciónde normas sustanciales y procesales en el ejercicio del ius puniendi frente a menores infractores en Colombia (2018)
The Childhood and Adolescence Code, establishes penalties for juvenile offenders in Colombia, which are ambiguous and also to implement the interpreter should refer to the Criminal Code, Code of Criminal Procedure, Rules of International Law, among others, often creating difficulty analysis, application of substantial standard pricing penalties, use of procedures, among other difficulties that are evident in legal practice, especially at the stage of investigation and prosecution, therefore in this research paper will develop the next question: Is there a need to unify the substantive and procedural rules for the application of the criminal law against young offenders in Colombia?. In conclusion, it must be to be dispersed standards childhood in different codes, domestic laws, international treaties and agreements, it is necessary to unify a code which integrates all rules aimed at children and adolescents in order to facilitate the interpretation and implementation in the respective criminal proceedings, even has the same Constitutional Court and the Attorney General’s Office have urged Congress to unify the rules of childhood and adolescence. © 2018, Corporacion Universitaria Republicana. All rights reserved.